Pasambahan Makan pada Upacara Perkawinan di Nagari Talang Babungo Kecamatan Hiliran Gumanti Kabupaten Solok - Siska W., Maitra Wike; Juita, Novia; Amir, Amril (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2012)
This article aims to describe the structures, functions, and context of appreciation for dinner (pasambahan makan) at marriage ceremony in Talang Babungo Hiliran Gumanti Solok regency. The data of this observation is expression of appreciation for dinner. The souces data of this observation are expression of appreciation for dinner at wedding party of Ronalvi dan Helmita Rahma Tullah. These data are collected by use of free listening copy out technigue, interview technigue, copy technigue and writing technigue as advanced technigue. The observation contents are expression of appreciation structure, opening speech, content and klosing. These are six funcition of expression of appreciation that is found. There are: religion function, custom function, moral function, education function, language function and social function. The expressions of appreciation have two context, there are situation context and context.